Serological prevalence of bovine viral diarrhoea (BVD-1) in non-vaccinated dairy cattle in the municipality of Realeza-Paraná - Anderson, Bedin; Sott, Tatiane; Da Costa Freitas, Fagner Luiz; Nascif, Iucif Abrão; Rozolen, Juliana Moreira [UNESP]; Fonseca-Alves, Carlos Eduardo; Elias, Fabiana (Universidade Estadual de Londrina, 2020)
Bovine viral diarrhoea (BVD) is an infectious and contagious disease affecting cattle that is responsible for causing a wide range of clinical manifestations ranging from inapparent or subclinical infections to an acute and sometimes fatal disease known as mucosal disease. The agent that causes BVD is an RNA virus of the genus Pestivirus and family Flaviridae. BVD is transmitted in two different ways: horizontal, by secretions, and vertically in pregnant cows, where the cow transmits the virus to the foetus. The clinical signs depend on the affected animal, its immunological capacity, and in the case of pregnant females, the gestation phase. A gestational infection can result in several changes, such as congenital anomalies, abortion, or even the birth of so-called persistently infected (PI) animals, which are difficult to detect and have a very important epidemiological role within the herd. The southwest region of Paraná has the largest dairy basin in the state of Paraná and is predominantly composed of family farmers, many of whom adopt measures that increase the health risk of their herd. The objective of this study was to delineate the serological prevalence of non-vaccinated dairy cattle in the municipality of Royalty-PR in relation to the BVD-1 virus, as well as to evaluate the odds ratios, relative risk and risk attributable to the independent variables of breed, age and the community under study. To that end, 317 blood serum samples from non-vaccinated cows from 18 different farms, with various breeds and ages, were evaluated by virus neutralization for the detection of antibodies specific to BVD-1. The results showed that 17.03% of the animals (54/317) had positive BVD-1 serology, and 82.33% (15/18) of the farms had at least one positive animal. Animals of the Jersey breed and the Barra do Sarandi Line community had the highest epidemiological risks, with a strong association with BVD-1 infection.
Keywords: Family farming; Reproduction; Sanitary; Southwest Paraná